Price versus Quantity Competition with Cost Sharing - Luca Lambertini; Dan Sasaki; Sougata Poddar (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
We inspect the interlink between the endogenous choice of price- and quantity- setting behavior in an oligopolic market, and cost sharing among oligopolists. A typical situation of this sort is an oligopoly game where firms invest in product development first, and ten play a marketing game later. Only in the initial investment stage ,the firms set up a joint venture in order to share the costs. We discover that, in the presence of shared costs, the well-established result by Singh and Vives (1984) that firms endogenously choose quantity (resp., price) as a dominant strategy when their products are substitutes (resp., complements) may not be the only equilibrium outcome. In particular, the procedural order between firms` cost sharing decisions and their marketing decisions make a key difference in the resulting equilibrium profiles.
Keywords: 330